IMPLEMENTATION OF KIRKPATRICK LEVEL REACTION AND LEARNING EVALUATION IN ENTREPRENEURSHIP TRAINING FOR YOUNG FARMERS AT BBPP LEMBANG - Septriani, Wieni Nur; Ardiwinata, Jajat Sudrajat; Saripah, Iip (Indonesian Journal of Adult and Community Education, 2022)
Evaluation must be carried out systematically and continuously in order to find out the results in comparing benchmarks to get improvement. For the success of a training, it is necessary to carry out a training evaluation. This study examines the Implementation of Kirkpatrick's Evaluation of Reaction Levels and Learning in Entrepreneurship Training for Young Farmers at BBPP Lembang, using Kirkpatrick's theory. This study aims to describe Kirkpatrick's evaluation at levels 1 and 2. This research is a descriptive qualitative. The subject of this study used a purposive sampling technique, namely in taking samples of data sources through certain considerations, those who were considered to know best about what actually happened in the field, making it easier for researchers to find out the object under study. Data collection techniques by means of observation, in-depth interviews and documentation studies. After that, understand the results of the data collection technique and then draw conclusions. The results showed that: evaluation of level one training, namely the reaction, there were variations in training reactions. Some were satisfied with the training, but there were still participants who felt unsatisfied with the training provided. Participant satisfaction reactions can be increased regarding the facilities and closeness between the instructor and the training participants. After that, the second level evaluation is learning that the participants achieved the desired goals and succeeded in carrying out the training activities, but the participants felt that the material provided was mostly in accordance with their needs. Participants want the instructors to be provided not only from BBPP but also to bring business practitioner instructors directly into the class